1985
DOI: 10.1002/bdd.2510060303
|View full text |Cite
|
Sign up to set email alerts
|

First‐pass elimination of lidocaine in the rabbit after peroral and rectal route of administration

Abstract: Lidocaine shows pronounced first-pass metabolism upon peroral administration in man (about 30 per cent peroral bioavailability). Since the rectal bioavailability is about 65 per cent in man it is assumed that some drug is directly absorbed into systemic circulation by-passing the liver. In rats peroral bioavailability is about 8 per cent whereas rectal bioavailability is about 100 per cent. This indicates that the rat is not a suitable model to study rectal lidocaine dosage forms. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…enters whole body blood directly, bypassing the portal circulation. Ritschel et al [5] estimated an f nh of 29.7% (range 5 -50%) from respective EBA (oral 6%, rectal 34%), assuming complete absorption via oral and rectal routes. In our experiments, the EBA (average of 60%) as well as f nh of rectal administration was considerably higher.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…enters whole body blood directly, bypassing the portal circulation. Ritschel et al [5] estimated an f nh of 29.7% (range 5 -50%) from respective EBA (oral 6%, rectal 34%), assuming complete absorption via oral and rectal routes. In our experiments, the EBA (average of 60%) as well as f nh of rectal administration was considerably higher.…”
Section: Resultsmentioning
confidence: 99%
“…The rabbit has been frequently used as an experimental system in the development of preparations for rectal administration and studies of drug metabolism [1]. Ritschel et al [5] reported that avoidance of hepatic first-pass effect was about 30% assuming complete absorption of lidocaine by oral and rectal routes. Gastric contents and type of preparation, however, are likely to affect absorption [6,7], and the above assumptions may not be accurate.…”
Section: Introductionmentioning
confidence: 99%